A Case with Anti TNF- α Induced Bullous Pemhigoid - Özlem Altındağ,; Ali Aydeniz,; Savaş Gürsoy, (Archives of Rheumatology, 2010)
Tumor necrosis factor-alpha (TNF-α) plays a crucial role in the development of autoimmune diseases, and anti-TNF-α agents are used in the treatment of this group of diseases. However, some adverse events such as various autoimmune diseases can occur with use of these agents. In this report, we present a female case who was diagnosed as bullous pemphigoid while receiving adalimumab for rheumatoid arthritis. (Turk J Rheumatol 2010; 25: 214-6)